Thymbra capitata Essential Oil Prevents Cell Death Induced by 4-Hydroxy-2-Nonenal in Neonatal Rat Cardiac Myocytes - Hortigón-Vinagre, María P.; Blanco, José; Ruiz, Trinidad; Henao, Fernando (Planta Medica, 2014)
An interdisciplinary experimental investigation on the antioxidant activity of Thymbra capitata essential oil was made. This plant is a Mediterranean culinary herb, whose essential oil antioxidant power has recently been demonstrated in vitro as one of the highest in nature. We tested if this in vitro antioxidant capacity was reproducible on biological systems using as model system primary cultures of neonatal rat cardiomyocytes treated with the lipid peroxidation product 4-hydroxy-2-nonenal. The composition and the in vitro antioxidant activity of the T. capitata essential oil were also assessed. Cell viability, mitochondrial membrane potential, and reactive oxygen species level were measured in cells treated with pathophysiologic doses of 4-hydroxy-2-nonenal (< 10 µM) or vehicle after being pre-incubated with small concentrations of the T. capitata essential oil, and the ability of small doses (< 40 ppm) to prevent the death of neonatal rat cardiomyocytes proved very remarkable. Long-term pre-incubation (12 h) with 20 ppm prevented 4-hydroxy-2-nonenal-induced cell death and avoided mitochondrial membrane potential loss and reactive oxygen species generation caused by 4-hydroxy-2-nonenal. A deleterious effect was shown at doses higher than 40 ppm. The results of this study pave the way to further analysis in animal models to achieve a deeper understanding of the in vivo antioxidant power of T. capitata essential oil.
Keywords: antioxidant; cardiomyocyte; essential oil; hydroxynonenal (HNE); Thymbra capitata; Lamiaceae; ROS